Assessing the Challenges of Information, Communication and Technology Education in the Rural Communities of Ghana: A Case of Sekyere South District - Elvis Kwakye Adomako; Charles Quansah; Ronald Osei Mensah (Mediterranean Journal of Social Sciences, 2022)
The Ghanaian government developed and implemented an ICT in Education Policy in 2008. ICT was integrated into instructing and education at all levels of the country's educational system as a result of this approach. This study looks at the challenges that rural communities in Ghana confront in securing the benefits of ICT in tutoring at various levels. The study used a sample size of 142 ICT instructors and heads of schools, as well as a small number of students, with a 90% confidence level. The district's respondents were chosen using planned and practical sampling methods. A structured form was used to gather primary data from all participants; however, only 93.67 percent responded. With the use of SPSS, tables were used to examine the primary data. According to the students, the number of hours per week dedicated to teaching ICT in schools is positively connected with their dedication to learning ICT. In terms of the impact of ICT on students' daily lives in the district, the reading discovered that ICT instruction had both beneficial and adverse consequences for kids. Based on the findings, the various stakeholders in education should conduct periodic on-the-job training for all teachers on evolving e-learning high-tech and approaches to provide them with the necessary abilities to effectively teach ICT. Received: 29 April 2022 / Accepted: 29 June 2022 / Published: 5 July 2022